Who is afraid of the asset quality review? Potential losses and capital shortfalls in the European banking system - Thomas Bonczek; Clemens Fuest; Michael Schröder (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
The creation of a banking union is widely seen as a key element of institutional reforms towards more financial and economic stability in Europe. Its objective is to improve the effectiveness of banking regulation and supervision and to sever the link between the finances of national governments and the banks in the Eurozone, which was a destabilising force in the European debt crisis. A key element of the banking union is the creation of a single supervisory mechanism. At the end of 2014, the European Central Bank will take over the responsibility for banking supervision in the Eurozone. It will directly supervise the largest and systemically most important banks in the Eurozone, a group of approximately 130 financial institutions. Before assuming its new task the ECB intends to investigate the financial solidity of these banks in the framework of a `comprehensive assessment'. It is the objective of this assessment `to enhance the transparency of the balance sheets of significant banks in the euro area, and in so doing, to trigger balance sheet repair where necessary, as well as to strengthen confidence.' The asset quality review (AQR), a review of the quality of different types of assets including underlying collateral will be the most important element of this assessment. The assessment will be combined with a stress test. (...)
urn:nbn:de:bsz:180-madoc-372028
Keywords: 330